PETROGENESA DAN POTENSI MINERALISASI PADA GRANIT ANGGI, KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - , JUMIKO NOMPI SARIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
By administration, the research area was located in Anggi, Manokwari Regency, West Papua Province. The complex and cumber some tectonic order of Papua, and the un availability of the geological and geochemical adequate data about the the presence of Anggi Granite for the research area prompted the authors to being interested in doing this research. The purpose of this research was to determine the petrographic and geochemical characteristics of the rocks and is expected to provide a good information and knowledge about the petrogenesis formation on the Anggi Granite. The Anggi Granite consists of 3 (three) distribution of the intrusion body which is divided into 2 (two) granitic intrusions bodies type that is the granitic intrusions in the form of batholiths and stocks bodies, based on the granite appearance area size on the surface. Petrographic observations indicate there are three (3) different texture variants from all of the three granite intrusion. The differences are based on the presence of minerals and grain size of the granite constituent crystal. By the IUGS classification, Anggi Granite is classified into groups of granite. Anggi Granite is included in the S-type granitoid, while for alumina saturation index, Anggi Granite belong to peraluminous group. Granite Anggi is a granitoid with orogenic Syn-Collisional Granite (Syn-COLG) character. The magma source at Anggi Granite comes from the upper continental crust. The REE content of all Anggi Granite samples shows the same pattern and shape. Common pattern and shape indicates that Anggi Granite have the same magma source. The depleted Eu is caused due to a reduction of plagioclase mineral and the depleted Ti shows that there is a further crystallization fractionation of the origin magma. The REE content of weathering soil shows that there were an enrichment that occurs during the weathering process. The identification result of heavy minerals in the quartz sand deposits around the granite body shows the presence of several important minerals. Heavy minerals that associated with Anggi Granite is uraninite mineral which carries the uranium element. While the other heavy minerals that present but may not be directly associated by genesis with the presence of Anggi Granite is the corundum mineral.